Stool specimen for diagnosis of pulmonary tuberculosis in adults: a systematic review - Adnan Ansar; Mahamudul Hasan; Saima Sultana; KM Saif-Ur-Rahman; Sadia Afrin (BMJ Open)
Objective To assess the diagnostic accuracy of stool specimens to diagnose pulmonary tuberculosis (PTB) in adults.Design Systematic review.Data sources MEDLINE (Ovid), Embase (Ovid), Web of Science and the Cochrane database were searched from inception to 9 March 2023–10 March 2023 using a comprehensive search strategy; reference lists of selected articles and relevant review articles were manually searched.Eligibility criteria for selecting studies Studies in English reporting diagnostic performance of stool specimens against respiratory specimens using mycobacterial culture or smear microscopy or Xpert assay to diagnose PTB in adults were eligible for this systematic review.Data extraction and synthesis Two reviewers independently screened the retrieved citations and extracted data. The risk of bias and applicability of results were assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. Narrative data synthesis was performed.Results A total of 1658 citations were screened, and 28 full-text articles were assessed. Nine studies met the inclusion criteria. The reported sensitivity and specificity of stool culture varied between 21.4% and 63.9%, and 61.5% and 100%, respectively. In stool smear microscopy, sensitivities and specificities ranged from 12.1% to 53.9%, and from 79.5% to 100%, respectively. The reported sensitivities of PCR assays, including Xpert assays, ranged from 69.7% to 100%, with specificities ranging from 69.8% to 100%. Most of the studies had a low risk of bias and a low applicability concern in all domains.Conclusion This systematic review could not conclude on the diagnostic accuracy of stool specimens for PTB diagnosis in adults. Further studies are required to evaluate the accuracy of stool specimens in adults to enable meta-analyses in updates of this review as well as other systematic reviews.PROSPERO registration number CRD42021245203.